Upaya Peningkatan Pembelajaran Pendidikan Jasmani Materi Tenis Meja Kelas XI di SMA Negeri 4 Medan - Cyntia Anggraini; Samsuddin Siregar; Muhammad Yan Ahady; M. Fauzan Ritonga; Michael Situmorang; Vita Tanti Imelda Rumahorbo (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to determine the improvement of table tennis skills of grade XI students of SMA Negeri 4 Medan through the application of drill, demonstration, and direct practice methods in physical education learning. The study used the Classroom Action Research (CAR) method which was implemented in two cycles with 20 students as research subjects. Data collection was carried out through skills tests, observation, and documentation. The research instrument was a basic table tennis technique skills test which included forehand drive, backhand drive, and serve with assessments based on aspects of shot accuracy, ball control, motion coordination, and shot consistency. Data were analyzed descriptively by comparing the results in each learning cycle. The results showed an increase in the average score of student skills from 15.7 in the initial stage to 24.3 at the end of cycle II. This increase indicates that students experienced development in mastering basic table tennis techniques, especially in the aspects of shot control and motion coordination. Thus, the application of drill, demonstration, and direct practice methods made a positive contribution to the improvement of students' table tennis skills in physical education learning.